Methodology for Developing Students’ Knowledge of Pharmacokinetics in Higher Medical Education - Odiljonova , Aziza (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
Mastering pharmacokinetics remains a formidable challenge for medical students due to complex mathematical modeling. This study evaluates a multimodal, simulation-integrated teaching methodology designed to optimize the acquisition of applied clinical dosing principles. Operating via a prospective quasi-experimental design, 214 third-year medical students were stratified into a standard didactic control cohort (n=106) and a simulation-enhanced intervention cohort (n=108). The intervention utilized a flipped-classroom architecture coupled with dynamic virtual patient simulators. Results demonstrated substantial mastery within the intervention cohort, achieving a mean clinical application score of 88.4 ± 4.2 compared to the control group’s 72.5 ± 5.8 (p < 0.001). Longitudinal assessments revealed a significantly attenuated knowledge decay rate. Integrating dynamic simulations fundamentally reconstructs pedagogical frameworks, ensuring practitioners possess the analytical agility required to mitigate adverse drug events.